Everyday economics - Coulter, Steve (Croydon Agenda, 2017)
Much of economics is a top-down analysis that simplifies and reduces the huge varieties between individuals to a predictable range of characteristics that lend themselves to systematic analysis. This book eschews this conventional perspective, which sees national economies as simply agglomerations of the activities of millions of people, and instead explores the role played by the individual in the economy, in particular, how the individual experiences the economy. In so doing, the book is able to illuminate the economic landscape for the non-technical reader in a much more engaging and accessible way.
Keywords: Economics